The story of the Amulet - Nesbit, E. (Dell, 1987)
The last part of the trilogy featuring Cyril Anthea, Robert and Jane. Tells of their adventures when they try to find "The strongest charm in the world".
Completes the trilogy, of which the first two volumes are "Five Children and It", and "The Phoenix and the Carpet."
"A Dell yearling classic.
The last part of the trilogy featuring Cyril Anthea, Robert and Jane. Tells of their adventures when they try to find "The strongest charm in the world".
Keywords: Charms / Fiction.; Time travel / Fiction.